2006
DOI: 10.1007/s00441-006-0283-4
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural immunolocalization of IGF-1 and insulin receptors in rat pituitary culture: evidence of a functional interaction between gonadotroph and lactotroph cells

Abstract: We have investigated the expression of receptors for insulin and insulin-like growth factor 1 (IGF-1) in rat pituitary cells in vitro and examined the morphological and proliferative changes induced in adenohypophyseal cells by insulin and IGF-1. The proliferation of lactotrophs was determined by double-immunostaining for bromodeoxyuridine and prolactin. Incubation with insulin (10, 100 or 1000 ng/ml) or IGF-1 (5, 30 or 100 ng/ml) for 48 or 72 h significantly increased the number of lactotrophs undergoing mito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 43 publications
2
15
0
Order By: Relevance
“…Additionally, the pituitary gonadotroph expresses insulin receptors (Gutierrez et al 2007, Soldani et al 1994). While most of the studies using the LβT2 model system have suggested an augmentation of Lhb expression there are some differences obtained by different groups that should be noted.…”
Section: Insulin Regulation Of Neuroendocrine Functionmentioning
confidence: 99%
“…Additionally, the pituitary gonadotroph expresses insulin receptors (Gutierrez et al 2007, Soldani et al 1994). While most of the studies using the LβT2 model system have suggested an augmentation of Lhb expression there are some differences obtained by different groups that should be noted.…”
Section: Insulin Regulation Of Neuroendocrine Functionmentioning
confidence: 99%
“…In addition, a series of evidence obtained by in vitro studies has also verified the effects of insulin on the proliferation of neural tissues, as in an in vitro study, the proliferatory effects of insulin were determined in pituitary cell culture and it was reported that incubation with insulin causes the number of lactotroph cells which undergo mitosis to increase, and this insulin-induced increase in proliferation was abolished when it was coincubated with the receptor tyrosine kinase inhibitor "genistein." Since insulin has stimulatory effects on protein synthesis by gonadotroph cells, it has been suggested that insulin-induced increase in lactotroph proliferation may be meditated indirectly by factors which are synthesized by gonadotroph cells [234]. Insulin has also been shown to regulate the proliferation and differentiation of multipotent neural stem cells, such as hippocampal neural stem cells, as insulin withdrawal causes these cells to undergo nonapoptotic, autophagic cell death demonstrated by cell morphology, PI staining, and proliferation assay [235].…”
Section: Proliferationmentioning
confidence: 99%
“…It has been established that gonadotrophs express insulin receptors on the cell surface and that L␤T2 cells are able to bind insulin (4,17). We and others have demonstrated that insulin augments GNRH-mediated Lhb expression and LH secretion primarily via induction of Egr-1 (1,4,40).…”
mentioning
confidence: 77%